"We don't do credit", Nijera Kori, social mobilisation and the collective capabilities of the poor in rural Bangladesh - Kabeer, Naila (Dhaka : Nijera Kori, 2002)
On the activities of Nijera Kori, non-governmental organization of Bangladesh and its impact on the economic conditions of rural poor of Bangladesh; a study.
Includes bibliographical references (p. 94-96).
Keywords: Nijera Kori (Organization); Non-governmental organizations -- Bangladesh; Rural poor -- Bangladesh